Wing Damage and Size Reduction in Drosophila melanogaster Caused by Bisphenol A - Zahrah Natasya Adiba; Ramadhan Muhamad Justitia; Kharomah Sinta; Kharomah Sindi; Choirunisa Nindiana; Zubaidah Siti; Fauzi Ahmad (BIO Web of Conferences)
Bisphenol A (BPA) often contaminates human food, although it is indicated to have negative impacts on health. This study aims to investigate the effect of BPA exposure on the wing morphology of Drosophila melanogaster. The flies were exposed to BPA at concentrations of 0.25 mg/mL and 0.5 mg/mL for one generation, with four replicates each treatment. For wing damage measurements, 160 flies were randomly selected and observed from each strain and each treatment, while the wing length parameter involved 10 male flies in each group. An Olympus SZ61 series stereo trinocular microscope was used to observe the wings, while an Olympus EP50 camera was used to document the wings. As a result, wing damage was observed in each strain exposed to BPA, both at 0.25 and 0.5 mg/mL levels. For wing length, both right and left wings, this parameter was only affected by the type of strain. These findings contribute to a better understanding of the potential health impacts of BPA.